Triceps Repair and Restoration of Triceps Footprint With Anchorless Suture Fixation. Issue 3 (September 2018) - Steffes, Matthew; Tayne, Samantha; Osmani, Feroz; Edwards, Gary; MacGillis, Kyle; Kim, Walter; Hammarstedt, Jon E.; Goldberg, Benjamin
Abstract : Triceps tendon rupture is an uncommon yet potentially devastating injury affecting patients over a broad demographic. Surgical treatment is essential to restore upper extremity functional status, and a vast array of techniques has been implemented with different fixation devices including suture buttons, intraosseous anchors, and suture repairs. Outcomes of distal triceps tendon repair have demonstrated nearly full return of functional capacity. Complications include infection, ulnar nerve neuropathy, arthrofibrosis, flexion contracture, hardware irritation, and most commonly, repair failure. We illustrate a triceps repair technique with suture fixation that restores the tendinous footprint without need of an adjunctive device.